Machiavelli, marketing and management : revisited - Harris, Phil, 1952-; Lock, Andrew, 1947-; Rees, Patricia (Routledge, 2025)
This second fascinating and cutting-edge text provides insight into the meaning and interpretation of Machiavelli and his works for management, marketing, and political thought and highlights their particular relevance to the manager and policymaker today. By bringing together contributions from authors, both academic and practitioner, this book addresses a number of common themes relating to the influences and arguments of perhaps the first political scientist and advocate of sound management and marketing principles.The volume covers a wide range of topics, including modern management and leadership, public affairs, technology, marketing, populist and fascist governments, and strategic corporate philanthropy.Machiavelli, Marketing and Management: Revisited will be of great interest to all practitioners, students, and scholars of management, marketing, political science, and public affairs.